KOMPETENSI PEDAGOGIK KETELADANAN PADA PENDIDIKAN ANTIKORUPSI DI PROVINSI LAMPUNG - Aida Zulaiha; Babang Robandi (Refleksi Edukatika)
This study aims to analyze the pedagogical competence required for character education development, particularly in PAK, and the importance of role modeling in its success.